A SONG – AUTHOR RELATIONSHIP EXTRACTOR FOR VIETNAMESE NEWS ARTICLES - Tuan-Nguyen, Hoai-Duc; Doan-Thi, Thanh-Quyen; Tran-Thi, Mi-Ni; Ho, Bao-Quoc (Vietnam Journal of Science and Technology, 2012)
Relationship extraction is a vital task which is required for many research fields such as Ontology construction or Q – A systems. Good results have been reached for widely used languages such as English while the achievement for Vietnamese is still limited. This paper presents a relationship extractor for Vietnamese which is trained with semi-supervised learning. A set of metrics is employed to qualify extraction result. And a simple NER system is integrated to boost the extractor’s efficiency.